TINGKAT PENGETAHUAN DAN SIKAP IBU TENTANG KEJADIAN RUAM POPOK PADA BAYI DI BPS ZULFIAH SURABAYA - Hermina Humune (Akademi Kebidanan Griya Husada Surabaya, 2018)
Diaper rash, also called diaper dermatitis, is a skin disorder (skin rash) that results from inflammation in diaper-covered areas, namely in the genitals, around the anus, buttocks, folds of the thighs and lower abdomen. This disease often occurs in infants and toddlers who use diapers, usually at the age of less than 2 years (Tjokronegoro, A., 2000: 19).Based on preliminary studies at BPS Ny. Retno Soepomo Surabaya on April 25, 2018 found 10 babies who came to BPS Zulfiah Surabaya and as many as 7 babies (69.97%) had diaper rash. Even though diaper rash should not occur in infants. The purpose of this study was to describe the knowledge and attitudes of mothers with the incidence of diaper rash in infants.Method: using descriptive method with quota sampling technique, which is taken by specifying a number of sample members in the April 2018 period by using a questionnaire as a research instrument. The data analysis technique uses frequency tables and cross tabulations with the population are all mothers who came to check their babies at BPS Zulfiah Surabaya. Results: the results of the study were obtained by mothers with good knowledge (17.5%), sufficient knowledge (32.5%) and lack of knowledge (50%). Whereas from the attitudes obtained strongly agree (7.5%), agree (20%), disagree (25%) and strongly disagree (47.5%) Discussion: Conclude that mothers who have less knowledge , the majority of their babies experience diaper rash. This is influenced by the mother's ignorance about how to properly care for the baby. Health workers are expected to be able to provide information about how to care for babies properly so that diaper rash does not occur in infants.